Bewässerungslandwirtschaft in Kalifornien und den Great Plains.: Anpassungsstrategien an Dürrejahre und die Erschöpfung von Grundwasservorräten - Windhorst, Hans-Wilhelm; Klohn, Werner (ERDKUNDE, 1996)
In 1992 about 11. 3 percent of the cropland in the United States were irrigated. In California and in the southern and central Great Plains irrigated agriculture has a high share of plant production. This paper analyzes the impacts of the drought from 1987 to 1992 on California's agriculture and overall economy. They are compared with the impacts that the depletion of the Ogallala aquifer or the decrease of the water table in large parts of the aquifer has had and will have in the future on the structure and production goals of agriculture. It can be shown that the lasting drought led to specific adaption processes in California. The available water was used to save the vineyards and orchards and for irrigation of cash crops. Nevertheless the financial losses amounted to several billion US-$, thousands of jobs were lost, especially in the southern part of the Great Valley. By means of a State Drought Water Bank the state government tried to make water available for the agglommerated areas in southern California as well as for the irrigation districts with the highest water shortage. This institution has been very successful. In 1992 the Central Valley Project Improvement Act was passed. Concerning water deliveries, in this act the same status was given to environmental protection as to agricultural and urban water users. Agriculture will lose about 7 percent of its present water supply, so the reduction of irrigated land will be inevitable. In the southern and central Great Plains the availability of water will decrease over several decades. Due to the increased pumping of groundwater from the Ogallala aquifer, the water table has dropped sharply over the last decades. Public action on the state, regional, and local level resulted from this development. Legal regulations on groundwater pumping differ in the Great Plains states. In this paper the regulations in Kansas and the water management programs in the southwestern part of the state are analyzed, also forseeable developments in cropping patterns, ongoing changes in animal production, and proposals for the future development of agriculture.